2022
DOI: 10.1111/nph.17973
|View full text |Cite
|
Sign up to set email alerts
|

A SPX domain‐containing phosphate transporter from Rhizophagus irregularis handles phosphate homeostasis at symbiotic interface of arbuscular mycorrhizas

Abstract: Reciprocal symbiosis of > 70% of terrestrial vascular plants with arbuscular mycorrhizal (AM) fungi provides the fungi with fatty acids and sugars. In return, AM fungi facilitate plant phosphate (Pi) uptake from soil. However, how AM fungi handle Pi transport and homeostasis at the symbiotic interface of AM symbiosis is poorly understood.Here, we identify an SPX (SYG1/Pho81/XPR1) domain-containing phosphate transporter, RiPT7 from Rhizophagus irregularis. To characterize the RiPT7 transporter, we combined subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 89 publications
1
39
0
Order By: Relevance
“…Recent studies also revealed that AMF possess various key genes involved in the phosphate response signal transduction pathway ( Salvioli et al, 2016 ; Venice et al, 2020 ). However, molecular mechanisms of phosphate transport and metabolism are still need further study ( Xie et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies also revealed that AMF possess various key genes involved in the phosphate response signal transduction pathway ( Salvioli et al, 2016 ; Venice et al, 2020 ). However, molecular mechanisms of phosphate transport and metabolism are still need further study ( Xie et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…AM-inducible plant PHT1 family P i transporters localized in the PAM are responsible for the P i uptake from the PAS; once the formation of arbuscules in symbiotic roots were blocked, the free P i within the intraradical mycelium (IRM) could not be transported to plant cells through the symbiotic interface, resulting in the accumulation of polyphosphate (polyP) in AM fungal vesicles ( 44 46 ). Therefore, to further investigate whether the knockdown of EgPT8 by RNAi affects P i transport in intraradical hyphae, we performed the expression analysis of the genes involved in the PHO pathway of R. irregularis in control and RNAi lines through qRT-PCR (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Drought stress reduces the transfer of P from soil to roots and subsequently to stems by reducing the transpiration rate and altering the function of membrane transporters ( Cramer et al, 2009 ). But AM fungi inoculation can enhance all these parameters ( Xie et al, 2022 ). Our study found that the P content in leaves and roots of P. cathayana seedlings inoculated with AM fungi increased significantly with the P additional level under the WW and WD conditions, which was significantly higher than the no-inoculated seedlings.…”
Section: Discussionmentioning
confidence: 99%